Students' Perception of the Use of Instagram as Mobile Learning in EFL Classroom - Muhammad Syafi'i; Paidi Gusmuliana; Rahma Ramadhani (UNIB Press, 2024)
This study's primary goal is to ascertain how students at UIN Sultan Syarif Kasim Riau's Department of English Language Education feel about using Instagram to help them learn vocabulary. This study uses a descriptive design and a qualitative methodology. The study involved 20 informants who were selected through purposive sampling, all of whom were first-semester students at the English Education Department of UIN Sultan Syarif Kasim Riau. Interviews were used by the researcher to gather data. Several benefits and drawbacks that students saw with Instagram use. In general, all students believe that Instagram accounts dedicated to learning English can aid and encourage their vocabulary acquisition. The explanation of the accounts was simple to understand, and students can learn whenever and wherever they choose because it is backed by engaging content. The flexibility of learning appeals to the students. As English majors, it can be extremely beneficial to them and help with their studies.